Cisplatin‐induced programmed cell death ligand‐2 expression is associated with metastasis ability in oral squamous cell carcinoma. Issue 4 (29th February 2020) - Sudo, Shunichi; Kajiya, Hiroshi; Okano, Shinji; Sasaki, Mina; Katsumata, Yuri; Ohno, Jun; Ikebe, Tetsuro; Hiraki, Akimitsu; Okabe, Koji
Abstract: Programmed cell death ligands (PD‐Ls) are expressed in tumor cells where they bind to programmed cell death‐1, an immunocyte co–receptor, resulting in tumor cell evasion from the immune system. Chemotherapeutic drugs have been recently reported to induce the expression of PD‐L, such as PD‐L1, in some cancer cells. However, little is known regarding PD‐L2 expression and its role in oral squamous cell carcinoma (OSCC). In this study, we examined the effect of cisplatin on the expression and regulation of PD‐L2 in OSCC cell lines and analyzed malignant behavior in PD‐L2‐expressing cells using colony, transwell and transformation assays. In addition, we examined PD‐L2 expression in the tumor tissues of OSCC patients using cytology and tissue microarray methods. In OSCC cell lines, cisplatin treatment upregulated PD‐L2 expression, along with that of the drug efflux transporter ABCG2, via signal transducers and activator of transcription (STAT) 1/3 activation. Moreover, PD‐L2‐positive or PD‐L2‐overexpressing cells demonstrated upregulation in both invasion and transformation ability but not in proliferation compared with PD‐L2‐negative or PD‐L2‐silencing cells. PD‐L2 expression was also observed in OSCC cells of cytology samples and tissue from OSCC patients. The intensity of PD‐L2 expression was correlated with more malignant morphological features in the histological appearance and an invasive pattern. Our findings indicate that cisplatin‐upregulated PD‐L2 expression in OSCC via STAT1/3 activation and the expression of PD‐L2 are likely to be associated with malignancy in OSCC. The PD‐L2 expression in cisplatin‐resistant OSCC cells may be a critical factor in prognosis of advanced OSCC patients. Abstract : Our findings indicate that cisplatin‐upregulated PD‐L2 expression in oral squamous cell carcinoma (OSCC) cells via STAT1/3 activation and the expression of PD‐L2 are likely to be associated with malignancy in OSCC. The PD‐L2 expression in cisplatin‐resistant OSCC cells may be a critical factor in the prognosis of advanced OSCC patients.